MANAJEMEN IMPRESI PADA PEREMPUAN PENARI TRADISIONAL MELALUI MEDIA SOSIAL : (STUDI PADA AKUN INSTAGRAM @ayodyapala) - Astagini, Nuria; Bangun, Cendera Rizky Anugrah (Jurnal Studi Komunikasi dan Media, 2023)
In Indonesia, the profession of traditional dancers is still categorized as a less classy profession. One organization that actively tries to weaken the negative image associated with traditional women dancers is the Ayodya Pala Art and Dance Studio. Through their Instagram account @ayodyapala, the management of the Ayodya Pala Arts and Dance Studio has implemented an impression management strategy to construct a positive image of their members as traditional dancers who are professional, multi-talented, educated, and well-mannered. Through qualitative data collection from five informants who are members of the Ayodya Pala Arts and dance studio, it is known that the assertive impression management strategy used to construct a positive image of women traditional dancers in the Instagram account @ayodyapala. These were identified through the content uploaded to the @ayodyapala Instagram account. The data also showed that the informant realized the importance of the Instagram algorithm as a curator that distributed content to other Instagram users. Therefore, the impression management strategy is being combined with other strategies, such as uploading content on a scheduled basis and using hashtags to increase the visibility of the uploaded content.